2018
DOI: 10.1007/s13238-018-0513-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of natural compounds targeting Annexin A2 with an anti-cancer effect

Abstract: Annexin A2, a multifunctional tumor associated protein, promotes nuclear factor-kappa B (NF-κB) activation by interacting with NF-κB p50 subunit and facilitating its nuclear translocation. Here we demonstrated that two ginsenosides Rg5 (G-Rg5) and Rk1 (G-Rk1), with similar structure, directly bound to Annexin A2 by molecular docking and cellular thermal shift assay. Both Rg5 and Rk1 inhibited the interaction between Annexin A2 and NF-κB p50 subunit, their translocation to nuclear and NF-κB activation. Inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…that ANXA2 promotes NF‐κB activation by binding to NF‐κB p50 subunit with its N terminal sequences, increasing its transcriptional activity and upregulating the transcription of several target genes downstream of NF‐κB, including interleukin (IL)‐6, which contributes to anti‐apoptotic signalling (Jung et al., 2015). Wang et al., in 2018, demonstrated that two ginsenosides Rg5 (G‐Rg5) and Rk1 (G‐Rk1), with similar structure, directly bound to ANXA2 (Wang et al., 2018), inhibiting its interaction with the NF‐κB p50 subunit and leading to caspase activation and apoptosis. These studies demonstrated that inhibition of ANXA2 provided a new regulatory tool on NF‐κB activity and supported the notion that the inhibition of ANXA2 may be a suitable anti‐cancer therapy (Wang et al., 2018).…”
Section: Annexin A2 (Anxa2)mentioning
confidence: 99%
See 1 more Smart Citation
“…that ANXA2 promotes NF‐κB activation by binding to NF‐κB p50 subunit with its N terminal sequences, increasing its transcriptional activity and upregulating the transcription of several target genes downstream of NF‐κB, including interleukin (IL)‐6, which contributes to anti‐apoptotic signalling (Jung et al., 2015). Wang et al., in 2018, demonstrated that two ginsenosides Rg5 (G‐Rg5) and Rk1 (G‐Rk1), with similar structure, directly bound to ANXA2 (Wang et al., 2018), inhibiting its interaction with the NF‐κB p50 subunit and leading to caspase activation and apoptosis. These studies demonstrated that inhibition of ANXA2 provided a new regulatory tool on NF‐κB activity and supported the notion that the inhibition of ANXA2 may be a suitable anti‐cancer therapy (Wang et al., 2018).…”
Section: Annexin A2 (Anxa2)mentioning
confidence: 99%
“…Wang et al., in 2018, demonstrated that two ginsenosides Rg5 (G‐Rg5) and Rk1 (G‐Rk1), with similar structure, directly bound to ANXA2 (Wang et al., 2018), inhibiting its interaction with the NF‐κB p50 subunit and leading to caspase activation and apoptosis. These studies demonstrated that inhibition of ANXA2 provided a new regulatory tool on NF‐κB activity and supported the notion that the inhibition of ANXA2 may be a suitable anti‐cancer therapy (Wang et al., 2018).…”
Section: Annexin A2 (Anxa2)mentioning
confidence: 99%
“…Additionally, the expression levels of procaspase-8 and −9 decreased after the carriers-mediated Dz13 transfection, suggesting the activation of caspase-8 and −9 through the cleavage of their precursors. Basically, the activation of caspase-8 has been identified to play a critical role in the cell apoptosis through the death receptor-dependent pathway, while caspase-9 could initiate the cell apoptosis based on the mitochondria-dependent apoptotic pathway 39,40. Thus, we inferred that the carrier-mediated Dz13 transfection could trigger the cell apoptosis through both death receptor-dependent pathway and mitochondrial apoptotic signaling pathway.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, it was possible that C-K–induced downregulation of NF-кB activity was mainly mediated by Annexin A2. We have previously indicated that (20S)G-Rh2, G-Rg5, and G-Rk1 inhibited NF-κB activation targeting Annexin A2; however, a similar mechanism was not obtained to other ginsenosides such as (20S/R)G-Rg3, (20R)G-Rh2, protopanoxadiol (PPD), and protopanaxatriol (PPT) (data not shown) [25], [30]. These researches suggested that C-K acted as a specific binding molecule to Annexin A2.…”
Section: Discussionmentioning
confidence: 95%